Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm using the following definition:

A category $\mathcal C$ is given by the following:

  1. A collection of objects $A$
  2. A set $M(A, B)$ for any two objects $A, B \in \mathcal C$.
  3. A function $M(B, C) \times M(A, B) \to M(A, C)$ for each triple of objects $A, B, C \in \mathcal C$.

These terms must satisfy the following axioms

I: If $\alpha : A \to B$, $\beta : B \to C$ and $\gamma : C \to D$, then $\gamma(\beta \alpha) = (\gamma \beta)\alpha$.

II: For each $A \in \mathcal C$, there exists $i_A : A \to A$ such that if $\beta : B \to A$, $\gamma : A \to C$ then $i_A \beta = \beta$ and $\gamma i_A = \gamma$.

A category $\mathcal C$ shall be called a $K$-category where $K$ is a commutative ring with unity if it has a distinguished object 0, the zero object, and satisfies the following three axioms:

III: $M(A, B)$ is a unital $K$-module.

IV: The function $M(B, C) \times M(A, B) \to M(A, C)$ is a bilinear map of $K$-modules

V: $M(0, 0)$ is the zero module, also written 0.

The following theorem is what I am having trouble with. I can't seem to be able to get the result using the previous definition of $K$-category (From Swan's 'The Theory of Sheaves')

Prove: $M(0, A) = M(0, 0) = M(A, 0)$.

Proof:Since we know $M(A, B)$ is a set (moreover module) for any $A, B \in \mathcal C$, then it would suffice to show that $M(0, A) \subseteq M(0, 0)$ and $M(0, 0) \subseteq M(0, A)$. The latter inclusion is trivial since $M(0, 0)$ is the zero module and every module has the zero module as a submodule.

Now let $f \in M(0, A)$. We want to show that $f \in M(0, 0)$, but since $M(0, 0)$ is the zero module and it is an additive subgroup, its only element is the 'zero'-map such that the following two axioms hold: (Axioms of module)

  1. $f + 0 = f$ for all $f \in M(A, B)$
  2. $f + (-f) = 0$ for all $f \in M(A, B)$

Here is where I am stuck. I can't seem to get the result directly from using the axioms I was given. Any help?

As a sub-question (soft), does anyone have any opinions/recommendations on my choice of textbook on Sheaf Theory? This is my first introduction to the subject and I wanted a textbook that didn't have too much topology and this seemed great, but I've been finding a bit of types :(

share|cite|improve this question
up vote 2 down vote accepted

Let $f\in M(0,A)$. The axiom IV means in particular that $(f\cdot k)i_0=f(k\cdot i_0)$ for $k\in K$. Take $k=0$, then $0_A=fi_0$, i.e. $f=0_A$.

Remark: It is incorrect to write $M(0, A) \subseteq M(0, 0)$ since $M(A,B)\cap M(C,D)=\emptyset$ for $(A,B)\ne (C,D)$.

share|cite|improve this answer
Can you confirm: I understand how you use bilinearity. If you take $k=0$, then $f \cdot 0 = 0_A$ where $0_A$ is the zero element of the $M(0, A)$ module (property of modules, scalar times zero = zero of module), so $(f \cdot k)i_0 = 0_A i_0 = 0_A$. But then $(0 \cdot i_0) = 0_0 = i_0$ because $M(0, 0)$ only has one element, so $f(0 \cdot i_0) = f i_0 = f$, correct, showing $f = 0_A$? – Robert Cardona Sep 19 '13 at 13:34
More importantly, if I am not trying to show a double inclusion, then what am I trying to show? An isomorphism of modules? The both only have one element so that 'are' both the zero module, up to isomorphism? Thanks a lot :D – Robert Cardona Sep 19 '13 at 13:36
To 1st remark: Yes, you understand right. To 2nd remark: Yes, in both cases one should prove triviality of the modules. – Boris Novikov Sep 19 '13 at 14:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.